2000
DOI: 10.1038/77116
|View full text |Cite
|
Sign up to set email alerts
|

Widespread aneuploidy revealed by DNA microarray expression profiling

Abstract: Expression profiling using DNA microarrays holds great promise for a variety of research applications, including the systematic characterization of genes discovered by sequencing projects. To demonstrate the general usefulness of this approach, we recently obtained expression profiles for nearly 300 Saccharomyces cerevisiae deletion mutants. Approximately 8% of the mutants profiled exhibited chromosome-wide expression biases, leading to spurious correlations among profiles. Competitive hybridization of genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
365
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(383 citation statements)
references
References 24 publications
17
365
1
Order By: Relevance
“…The wild-type control strain used in that study was later shown to have a duplicated chromosome XIII, which resulted in all the genes on chromosome XIII seeming to be slightly down-regulated in a tup1⌬ strain (Hughes et al, 2000b). To correct for this strain abnormality and because microarray techniques and analysis have advanced since that first publication, we present a new set of expression microarray data for a tup1⌬ mutant.…”
Section: Deletion Of Tup1 Derepresses a Large Group Of Diverse Genesmentioning
confidence: 99%
“…The wild-type control strain used in that study was later shown to have a duplicated chromosome XIII, which resulted in all the genes on chromosome XIII seeming to be slightly down-regulated in a tup1⌬ strain (Hughes et al, 2000b). To correct for this strain abnormality and because microarray techniques and analysis have advanced since that first publication, we present a new set of expression microarray data for a tup1⌬ mutant.…”
Section: Deletion Of Tup1 Derepresses a Large Group Of Diverse Genesmentioning
confidence: 99%
“…Meanwhile improvements of RNA isolation and unbiased amplification of tiny amounts of mRNA (picogram) enable researchers to analyse RNA from single embryos [90]. With the aid of this technology one can gain in-depth insight into the proper functioning of a transgenic organism and thereby ensure the absence of unwanted side effects [88,89]. This would also be required to maintain the highest possible levels of animal welfare in cases of genetic modification.…”
Section: Precautions and Perspectivesmentioning
confidence: 99%
“…Furthermore, it should be kept in mind that the biomedical applications of farm animals will require strict standards of 'genetic security' and reliable and sensitive methods for the molecular characterization of the products. A major contribution towards the goal of well-defined products will come from array technology (cDNA, peptide or protein arrays), which establishes 'fingerprint' profiles at the transcriptional and/or protein level [88,89]. Meanwhile improvements of RNA isolation and unbiased amplification of tiny amounts of mRNA (picogram) enable researchers to analyse RNA from single embryos [90].…”
Section: Precautions and Perspectivesmentioning
confidence: 99%
“…The microarray datasets were investigated to test for chromosomal aneuploidy in the TCA cycle mutant strains (Hughes et al, 2000). Gene expression ratios from individual microarray experiments were sorted by chromosome, and the average expression for each chromosome was calculated to test for chromosome-wide expression bias indicative of chromosomal aneuploidy.…”
Section: Aneuploidymentioning
confidence: 99%